Zinc induces reactive astrogliosis through ERK‐dependent activation of Stat3 and promotes synaptic degeneration. Issue 6 (7th November 2021) - Huiliang, Zhang; Mengzhe, Yang; Xiaochuan, Wang; Hui, Wei; Min, Du; Mengqi, Wang; Jianzhi, Wang; Zhongshan, Chen; Caixia, Peng; Rong, Liu
Abstract: Reactive astrogliosis is an early event in Alzheimer's disease (AD) brain and plays a key role in synaptic degeneration in AD development. Zinc accumulates in extracellular fraction and synaptosomes in AD human brains with its effect on reactive astrocytes remaining unknown. Through Western blotting, Quantitative polymerase chain reaction (qPCR), and immunofluorescence detection on primary astrocytes treated by zinc and/or zinc chelator, we revealed that zinc induced harmful A1‐type reactive astrogliosis in cultured primary astrocytes; the latter, promoted synaptic degeneration in primary neurons. The mechanism investigation showed that zinc induced activation of extracellular regulated protein kinase (ERK) and Janus kinase 2 (JAK2), which phosphorylated signal transduction and transcription activator 3 (Stat3) at serine 727 (S727‐Stat3) and tyrosine 705 (Y705‐Stat3), respectively, resulting in activation of Stat3. Stat3 phosphorylation at S727 by ERK plays a key role in zinc‐induced astrogliosis. These data imply a new molecular mechanism of reactive astrogliosis in AD, in which excessive zinc activates Stat3 through up‐regulating ERK signaling pathway. Abstract : Zinc activates extracellular regulated protein kinases (ERK) to phosphorylate signal transduction and transcription activator 3 (Stat3) at serine 727 (S727), resulting in Stat3 activation and A1‐type astrogliosis. Zinc also activates Janus kinase 2 (JAK2) to induce phosphorylation of Stat3 at tyrosine 705 (Y705), but Stat3 phosphorylation at this site is not indispensable for astrocytes activation by zinc. The pro‐inflammatory factors released by active astrocytes promote synaptic degeneration in neurons.